Antara Like dan Self-Worth: Dampak Media Sosial Terhadap Konsep Diri dan Produktivitas Mahasiswa - Wijaya, Rafi Bagus Adi; Subakti, Agung (Jurnal Konseling dan Psikologi Indonesia, 2025)
Social media has become an integral part of university students' daily lives, affecting their self-worth, academic productivity and emotional well-being. This study explores two roles of social media, namely as a source of external validation and online social support, with a focus on its impact on students' academic and personal experiences. Using a descriptive qualitative approach, data was collected through in-depth interviews with three university students who actively use social media, as well as documentation of their social media activities. The results showed that social media interactions, characterised by likes, comments, and engagement, have a significant influence on students' self-worth. While providing emotional motivation and a sense of being valued, this reliance on external validation raises concerns about its impact on long-term self-confidence. In the context of academic productivity, an ambivalent relationship was found, where social media can enhance productivity through access to educational content, but often becomes a distraction due to its entertainment features. Online social support, while providing an emotional boost, was found to be less effective than face-to-face interactions in addressing deeper psychological needs. This study emphasises the importance of developing self-regulation and digital literacy among university students to optimise their use of social media in support of their personal growth and academic success.